Impact of systemic atherosclerosis on clinical characteristics and short-term outcomes in patients with deep venous thrombosis or thrombophlebitis - Keller, Karsten; Hobohm, Lukas; Münzel, Thomas; Lankeit, Mareike; Konstantinides, Stavros; Ostad, Mir Abolfazl (The American journal of the medical sciences, 2022)
Background - Venous thromboembolism (VTE) and atherosclerosis are accompanied by substantial cardiovascular mortality; links between both disease entities were reported. We aimed to investigate the impact of systemic atherosclerosis on adverse outcomes in patients with deep venous thrombosis or thrombophlebitis (DVT) and to identify differences in DVT patients with and without systemic atherosclerosis. - Methods - The German nationwide inpatient sample was used for this analysis. Patients admitted for DVT were included in this study and stratified by systemic atherosclerosis (composite of coronary artery disease, myocardial infarction, ischemic stroke, and/or atherosclerotic arterial diseases). We compared DVT patients with (DVT+Athero) and without (DVT-Athero) systemic atherosclerosis and analysed the impact of systemic atherosclerosis on adverse outcomes. - Results - Overall, 489,679 patients with DVT (55.7% females) were included in this analysis. Among these, 53,309 (10.9%) were coded with concomitant systemic atherosclerosis with age-dependent incline. Concomitant PE (4.1% vs.3.8%, P=0.001) was more frequently in DVT-Athero and risk for PE in DVT patients was independently associated with absence of systemic atherosclerosis (OR 0.87 [95%CI 0.83-0.91], P<0.001). In-hospital mortality (3.4% vs.1.4%, P<0.001) and adverse in-hospital events (2.2% vs.0.8%, P<0.001) were more prevalent in DVT+Athero compared to DVT-Athero; both, in-hospital mortality (OR 1.52 [95%CI 1.41-1.63], P<0.001) and adverse in-hospital events (OR 1.49 [95%CI 1.40-1.58], P<0.001) were affected independently of sex, age and comorbidities by systemic atherosclerosis. - Conclusions - Systemic atherosclerosis in DVT patients was accompanied by poorer outcomes. Systemic atherosclerosis was associated with higher bleeding rate and with isolated DVT (without concomitant PE).
Available online 20 September 2021, version of record 3 March 2022
Gesehen am 03.08.2022